The Influence of Brand Trust and Brand Image on Brand Loyalty of Sunlight Soap in Sidoarjo Regency - Ilham Muhammad Yusuf; Sugeng Purwanto (Journal of Social Research, 2023)
Along with the development of various industries to meet human needs, the tighter the competition of these various industries in influencing the public to choose their products. In the face of increasingly fierce competition and the increasing number of companies that have sprung up, companies must be able to determine effective and efficient marketing policies, especially to influence consumers to want to buy the products offered. The purpose of this study was to determine the effect of brand trust on Sunlight's brand loyalty. The results of this study are theoretically expected to add to the repertoire of knowledge in the field of economics related to marketing management, and be able to provide an understanding of the influence of Brand Trust and Brand Image on Brand Loyalty. The population in this study is users who have used Sunlight dish soap in the Sidoarjo regency area. The sampling used in this study was Users of Sunlight dish soap products in Sidoarjo Regency and Users Are Housewives. The data collection method carried out in this study is the questionnaire method. Sunlight or Sanlait is a dishwashing soap that removes grease faster and makes household appliances easier to clean. Brand trust is able to contribute well to the brand loyalty of sunlight product users in the Sidoarjo Regency area. This shows that the higher the brand's trust in the public in remembering the reuse of sunlight products, the greater the brand loyalty of sunlight dish soap.